Multi-rate transmissions on spectral amplitude coding optical code division multiple access system using random diagonal codes - Hilal Adnan, Fadhil; Syed Alwee Aljunid, Syed Junid; R.Badlishah, Ahmad (Institute of Physics, Wroclaw University of Technology, 2009)
Link to publisher's homepage at http://www.if.pwr.wroc.pl/~optappl/about.php